Synergistic effect of porous structure and gradient structure in carbon foam to boost terahertz absorption - Xiao Sun; Lipeng Wu; Congli Zhou; Dun Lu; Shangzhi Chen; Mingduo Yang; Chaoyang Kuang; Wenjie Fu; Xuesong Li; Zhaoyun Duan; Qiye Wen (Journal of Materiomics)
Creating porous structures and gradient structures are two commonly used design strategies for terahertz (THz) absorption enhancement. However, the synergistic effect of porous structure and gradient structure on THz absorption still remains less explored. Here, we took an almost non-conductive porous carbon foam as raw material, and fabricated an integrated gradient porous carbon foam (PCF) by microwave selective sintering. The experimental results show that the synergistic effect of the porous and gradient structures resulted in a 140% improvement in THz absorption performance. Specifically, an excellent average absorption intensity of −38.8 dB (absorptivity is about 99.99%) is obtained in the frequency range from 0.5 to 4.0 THz. COMSOL simulation and transmission line model were applied to explore the formation mechanism and the gradient loss capabilities of gradient structure. This work not only reveals the synergistic enhancement mechanism of porous and gradient structures for the THz absorption, but also provides new insights into the design of high-performance THz absorbers in the future.